Supraharmonic Pollution Emitted by Nonlinear Loads in Power Networks—Ongoing Worldwide Research and Upcoming Challenges - Łukasz Michalec; Paweł Kostyła; Zbigniew Leonowicz (Energies, 2022)
Researchers at many different institutions around the world study voltage and current waveform distortions in power networks using a variety of techniques. Due to the uncontrolled growing number of nonlinear devices supplied by electrical energy, more severe supraharmonic pollution has been observed. A bibliometric analysis of the topic development between 2013 and 2022 is presented in the paper. Using the selected search tools, a comparative review of articles published in the last three years was conducted. It organizes the existing knowledge about supraharmonic pollution generated by nonlinear devices and identifies current research challenges associated with the spread of these disturbances in electrical networks. The most frequently discussed topics by researchers are those that deal with the level of emissions generated by supraharmonic sources and their effects on components of the power system. The second most prominent research direction is the detection, measurement, analysis, and severity evaluation of supraharmonic pollution. Finally, the authors discuss areas of study related to the topic that offers perspectives for future research. The impact of high-frequency component pollution generated by nonlinear loads on emissions intentionally designed to carry communications signals through electrical networks needs to be explored under various power supply conditions.